Effect of freezing wheat dough enriched with calcium salts with/without inulin on bread quality - Carboni, Angela Daniela (2022)
Bread is a popular food that is widely consumed worldwide but has a short shelf life. Besides that, when incorporating prebiotics and calcium, aging mechanisms accelerate, further shortening the shelf-life. The objective of this work was to evaluate the effect of freezing storage on the rheological (loss tangent, tan ) and thermal (glass transition temperature, Tg) properties of unfrozen dough, the fermentation times (tf), and the baking quality of wheat bread fortified with calcium and inulin. Formulations studied included wheat flour (control-C), flour with 1800 ppm Ca (calcium carbonate-CA, calcium citrate-CI or calcium lactate-LA), and flour with 2400 ppm Ca and 12% inulin (calcium carbonate-CA-In, calcium citrate-CI-In or calcium lactate-LA-In). Doughs were stored at −18 ◦C for 1, 7, 30 and 60 days. After storage, the rheological (oscillatory rheometry and texture profile analysis) and thermomechanical properties of the thawed doughs were measured. The quality parameters of breads determined consisted of specific volume (Vs), color, moisture, firmness, elasticity, and alveoli size characterization. Dough freezing neither changed viscoelasticity (tan ) nor decreased hardness and adhesiveness up to the values observed for fresh wheat dough. The Tg of dough with calcium carbonate increased, while for samples with organic calcium salts, it (citrate and lactate) decreased. The tf of thawed dough significantly increased. The Vs of all breads did not change during the first 30 days but decreased after freezing the dough for 60 days (p < 0.05), probably due to the death of the yeasts. Crumb moisture decreased over time, and in all cases crumb C had the highest moisture content, suggesting a dehydration effect of the calcium salt. The firmness of CA, LA and C crumbs were similar and higher than that of CI (p < 0.05), suggesting a destabilizing effect of CI anion on gluten proteins. Inulin contributed to the depreciation of bread quality, mainly at 60 days of dough freezing storage. It can be concluded that during freezing storage, calcium improves the dynamic elasticity of the dough, although under extreme conditions it generates loaves of smaller volume. Principal component analysis (PCA) explained 66.5% of total variance. Principal component 1 (PC1) was associated with dough properties, and accounted for 44.8% of the total variance. In turn, PC2 was mainly related to baking quality parameters (fermentation time, browning index, firmness and springiness of crumbs), and explained 21.7% of the total variance. Fortification with calcium citrate should be recommended for dough freezing, as breads with softer crumbs were obtained under such conditions.